2020
DOI: 10.3390/f12010026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bentonite on the Early Growth Characteristics of Teak Seedlings Planted in Sandy Soil in Northeast Thailand—A Pilot Study

Abstract: The growth of teak (Tectona grandis L. f.) seedlings in sandy soil in northeast Thailand is suppressed by infertility and drought stress. In a preliminary field pot experiment, we confirmed that bentonite was useful for increasing soil water availability. To monitor early growth characteristics of teak seedlings in sandy soil, we curried out an experiment of teak seedlings using bentonite and fertilizer in the field from July 2014 to November 2015. We then compared the growth, biomass, photosynthetic rate, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…Intercellular CO 2 concentration ranged between 475.0 ± 15.23 to 180.5 ± 6.49 µl l −1 indicating that higher intercellular CO 2 concentration associated with increased stomatal conductance affects the photosynthetic rate. Lower photosynthetic rate than the current investigation was documented in teak 11 13 , 33 , 42 , 46 , Similar noteworthy results were documented in Pawlonia tomentosa 47 , Eucalyptus species 48 , Tabebuia aurea 49 and Rubber 35 .…”
Section: Discussionsupporting
confidence: 90%
“…Intercellular CO 2 concentration ranged between 475.0 ± 15.23 to 180.5 ± 6.49 µl l −1 indicating that higher intercellular CO 2 concentration associated with increased stomatal conductance affects the photosynthetic rate. Lower photosynthetic rate than the current investigation was documented in teak 11 13 , 33 , 42 , 46 , Similar noteworthy results were documented in Pawlonia tomentosa 47 , Eucalyptus species 48 , Tabebuia aurea 49 and Rubber 35 .…”
Section: Discussionsupporting
confidence: 90%
“…It enhances nutrient holding capacity, improves soil structure and its moisture content and provides a better habitat for soil microorganisms. The positive impacts of bentonite on ameliorating sand properties and plant development were previously reported by Owen et al (2008) on Cotoneaster dammeri 'Skogholm ', Hazrati et al (2017) on Aloe vera, Paradalo et al (2019) on Lolium multiflorum, Kayama et al (2021) on teak (Tectona grandis), Younas et al (2022) on Bougainivillea sp., Satje and Nelson (2009) on sugarcane, AbdEl-Hamid et al (2013) on wheat and peanut, Mi et al (2020) on millet (Setaria italica), Karbout et al (2021) on date palm cv. Deglet Nour and Hassan et al (2022) on date palm cv.…”
Section: Introductionmentioning
confidence: 58%
“…In general, water use efficiency of A. vera increased with less water and more zeolite availability. On teak (Tectona grandis), Kayama et al (2021) observed that growth and plant dry mass were markedly increased by the application of bentonite and P-fertilizer to growth substrate. Moreover, the application of bentonite could mitigate drought stress in dry season.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of contact exchange, which releases H+ cationsinto the soil IOP Publishing doi:10.1088/1755-1315/1183/1/012045 2 solution, the absorption of cations by roots can also result in a drop in pH. The whole process of nutrient absorption may be affected to some extent by the pH value [3,4].…”
Section: Introductionmentioning
confidence: 99%